Relationship between metabolic syndrome and impulsivity in gambling disorder - Kazğan, Aslı; Yıldız, Sevler; Tabara, Muhammed Fatih; Atmaca, Murad (Journal of Dependence, 2021)
Objective: The present study aims to compare Metabolic Syndrome (MetS) parameters in pathological gambling disorder (PGD) patients and healthy controls and analyze the correlation between MetS and impulsivity levels in PGD patients with MetS diagnosis. Method: The present study was conducted with 74 PGD patients and 73 healthy controls. The sociodemographic data form and the Barratt Impulsivity Scale short form (BIS-11) were applied to all participants. The MetS parameters determined for all participants were analyzed based on to the National Cholesterol Education Program (NCEP) Adult Treatment Panel II criteria. Results: The total BIS-11 and subscale scores of the patient group were statistically significantly higher when compared to the control group. MetS rate in patients was higher than the control group with 58.1%. There was a significant correlation between diastolic blood pressures of the patients and motor impulsivity and unplanned impulse scores. SBPs, DBPs, TG and fasting blood levels of the patients were found to be significantly higher than the controls, while HDL levels were found to be significantly lower. Conclusion: PGD patients had higher impulsivity levels and MetS rates in these patients were higher than healthy controls. We think that our findings emphasize the consideration of impulsivity-based approaches in PGD treatment and attention to MetS in patients with PGD.